Gender-based violence and intersectional inequalities: Women with disabilities within the family and social structures in Chile. (Palimpsesto, 2025)
This article analyzes the multiple forms of violence faced by women with disabilities in Chile, through a critical review of secondary sources and an analysis of data from the IV National Survey on Violence Against Women (2020) and the III National Disability Study (2022). The findings show that these women experience higher, more persistent, and more complex levels of violence. The article examines the structural factors that sustain their exclusion in various spheres, such as home, work, and education. It concludes that violence against women with disabilities is a manifestation of interconnected oppressions -patriarchy, ableism, and neoliberalism- that demands comprehensive and transformative responses.Keywords: Disability, gender, intersectionality, violence, and inequality.
Keywords: Disability, gender, intersectionality, violence, and inequality.